Diagnosis of Cervical Intraepithelial Neoplasia and Invasive Cervical Carcinoma by Cervical Biopsy under Colposcopy and Analysis of Factors Influencing - Ying Wang; Jing Wang; Hua Mei (Emergency Medicine International)
Objective. To explore the diagnosis of cervical intraepithelial neoplasia (CIN) and invasive cervical carcinoma (ICC) by cervical biopsy under colposcopy and analyze the factors influencing the detection. Methods. The clinical data of 134 CIN confirmed by colposcopy biopsy in our hospital from June 2018 to October 2019 and subsequent LEEP treatment were analyzed retrospectively. All patients were diagnosed pathologically after the operation. The diagnosis of CIN by cervical biopsy under colposcopy was observed. The influencing factors of CIN and ICC detected by colposcopy biopsy were analyzed by the pathological results of loop electrosurgical excision procedure (LEEP) as the gold standard. Results. After LEEP, the number of the no intraepithelial or malignant lesions (NILM) or ICC were higher than that of colposcopy biopsy, and CIN-III was lower than that of colposcopy biopsy, the differences were all statistically significant (P<0.05). Among the 134 patients, the coincidence rate between colposcopy biopsy and LEEP examination results was 79.10% (106/134), and postoperative pathological findings showed that there were 13 cases (9.70%) with the pathological upgrade and 19 cases (14.18%) with pathological decrease. Multivariate logistic analysis showed that the image quality of colposcopy image, atypical blood vessels, biopsy sampling method, and visible lesion area of the cervix were the independent influencing factors for the detection of CIN and ICC by colposcopy biopsy (P<0.05). Conclusion. CIN and ICC can be diagnosed by colposcopy cervical biopsy and postoperative histopathology. However, there are still some missed and misdiagnosed cervical biopsies under colposcopy, and the combined detection of the two can further ensure the diagnosis rate. The clinical registration number is E2018091.